Genomic characterization, phylogenetic position and in situ localization of a novel putative mononegavirus in Lepeophtheirus salmonis - Økland, Arnfinn Lodden; Nylund, Are; Øvergård, Aina-Cathrine; Skoge, Renate Hvidsten; Kongshaug, Heidi (Archives of virology, 2019)
The complete genome sequence of a novel mononegavirus, Lepeophtheirus salmonis negative-stranded RNA virus 1 (LsNSRV-1), obtained from a salmonid ectoparasite, Lepeophtheirus salmonis was determined. The viral genome contains five open reading frames encoding three unknown proteins (ORF I, II and III), a putative glycoprotein (G), and a large (L) protein. Phylogenetic analysis placed LsNSRV-1 in the recently established mononegaviral family Artoviridae. LsNSRV-1 showed a prevalence of around 97% and was detected in all L. salmonis developmental stages. Viral genomic and antigenomic RNA was localized to nerve tissue, connective tissue, epithelial cells of the gut, subepidermal tissue, exocrine and cement glands, as well as the testis, vas deferens and spermatophore sac of male L. salmonis and the ovaries and oocytes of females. Viral RNA was detected in both the cytoplasm and the nucleoli of infected cells, and putative nuclear export and localization signals were found within the ORF I, III and L proteins, suggesting nuclear replication of LsNSRV-1. RNA interference (RNAi) was induced twice during development by the introduction of a double-stranded RNA fragment of ORF I, resulting in a transient knockdown of viral RNA. A large variation in the knockdown level was seen in adult males and off springs of knockdown animals, whereas the RNA level was more stable in adult females. Together with the localization of viral RNA within the male spermatophore and female oocytes and the amplification of viral RNA in developing embryos, this suggests that LsNSRV-1 is transmitted both maternally and paternally. Small amounts of viral RNA were detected at the site where chalimi were attached to the skin of Atlantic salmon ( Salmo salar ). However, as the RNAi-mediated treatment did not result in LsNSRV-1-negative offspring and the virus failed to replicate in the tested fish cell cultures, it is difficult to investigate the influence of secreted LsNSRV-1 on the salmon immune response.